2004
DOI: 10.1021/ma049300h
|View full text |Cite
|
Sign up to set email alerts
|

All-Cellulose Composite

Abstract: An all-cellulose composite, in which both the fibers and the matrix are cellulose, was prepared by distinguishing the solubility of the matrix cellulose into the solvent from that of the fibers through pretreatment. The structure, mechanical, and thermal properties of this composite were investigated using an X-ray diffraction, a scanning electron microscope, a tensile test, and dynamic viscoelastic and thermomechanical analyses. The tensile strength of uniaxially reinforced all-cellulose composite was 480 MPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
448
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 746 publications
(491 citation statements)
references
References 10 publications
11
448
1
6
Order By: Relevance
“…19,20 Individual singular nanofibers of cellulose exhibit low CTE, which is comparable to quartz glass, and an outstanding Young's modulus, which is higher than that of aluminum and glass fibers. 21,22 Although dense aggregates of cellulose nanofibers (CNFs) can form flexible, transparent films for electronic devices, [23][24][25][26] there currently are still substantial challenges to the practical application of CNF films, such as (i) incompatibility with high-temperature processing (o200°C), 27 (ii) optical haze (420% in visible light wavelengths) 28 derived from highly porous microstructures, (iii) poor water resistance (o28°in water contact angle), 26,29 (iv) difficulty in forming complex, fine shapes and (v) limits in mechanical stretchability. To the best of our knowledge, the potential of CNF to provide stretchable but reliable electronic devices is yet unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Individual singular nanofibers of cellulose exhibit low CTE, which is comparable to quartz glass, and an outstanding Young's modulus, which is higher than that of aluminum and glass fibers. 21,22 Although dense aggregates of cellulose nanofibers (CNFs) can form flexible, transparent films for electronic devices, [23][24][25][26] there currently are still substantial challenges to the practical application of CNF films, such as (i) incompatibility with high-temperature processing (o200°C), 27 (ii) optical haze (420% in visible light wavelengths) 28 derived from highly porous microstructures, (iii) poor water resistance (o28°in water contact angle), 26,29 (iv) difficulty in forming complex, fine shapes and (v) limits in mechanical stretchability. To the best of our knowledge, the potential of CNF to provide stretchable but reliable electronic devices is yet unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of temperature, pressure and time are very important in order to maintain optimum reinforcing effect of the fibres in SRC processing [6]. Various techniques such as hot compaction [7], partial dissolution [8], cool drawing [9] and chemical modification [10] have been employed to manufacture self--reinforced composites. Several studies have reported on the successful production of SRCs using a wide variety of polymer fibres, including polyethylene (PE) [11--14], polypropylene (PP) [15,16], polyethylene terephthalate (PET) [17], polyamides [18,19], polylactic acid (PLA) [4,20,21], polyglycolic acid (PGA) [22,23] and polymethylmethacryalate (PMMA) [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 All-cellulose composite (ACC) and nanocomposite (ACNC) have been studied for about a decade. 3 This class of biocomposites is manufactured from cellulose, which functions as both reinforcement and matrix. The matrix and reinforcement phases of this biocomposite are completely compatible with each other, allowing efficient stress transfer and adhesion at their interface.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of such composites can exceed those of glass-fiber composites. [3][4][5][6][7][8][9][10][11][12] Different solvents have been used to make ACC and ACNC, including N,N-dimethylacetamide/lithium chloride (DMAc/LiCl), 3,4,6,7 ionic liquid 8 and sodium hydroxide (NaOH)/urea. 9 DMAc/LiCl is especially popular because of its ability to dissolve cellulose under moderate conditions.…”
Section: Introductionmentioning
confidence: 99%